A note on the coefficient array of a generalized Fibonacci polynomial - Shannon, A. G.; Deveci, Ömür (Notes on number theory and discrete mathematics, 2020)
A particular version of a Fibonacci polynomial is presented and the coefficients are tabulated to bring out some of their number theory properties with known results. Generalizations of the fundamental and primordial Lucas sequences are used in the proofs.